Current Issues and Development Tendencies of the Right to a Healthy Environment in the EU Law - Radojčić, Stefan; Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
In the light of current global tendencies and a concern for the issue of environmental protection, this paper aims to provide an analysis of most important issues in this field, within the EU Law. Elements of a right to healthy environment are systematically regulated in the communitarian law. First, there is a long-standing normative activity of these issues, which in the last two years resulted in the adoption of new strategic documents. Second, jurisprudence of the ECJ has also followed development of the legislation, as well as circumstances in which those documents have been applied. Therefore, special attention is drawn to the newly-adopted general acts, created with long-term aims, and based on normative and factual experience over past decades. Its purpose is to achieve sustainable development goals in a mulitdimensional manner. Furthermore, an analysis of selected judgments of the ECJ shows the efficiency in application of relevant regulations and directives. Moreover, the intepretation of the EU law is of special importance, where the ECJ has a significan role. With regard to the universal character of this topic , the paper provides a short overview of the relevant legal framework in the USA, Norway and Serbia. Negotiations on the joining the EU imply the harmonizastion of domestic law with the standards of the communitarian law. By observing the Serbian environmental legal framework , it could be said that there is determination and concrete measures in the process of harmonization. On the basis of previuosly mentioned issues, authors structured the paper and aspects of the research contained therein, followed by the conclusions provided in the final chapter.